Antireflective and passivation properties of the photovoltaic structure with Al2O3 layer of different thickness. Issue 3 (2nd July 2018) - Swatowska, Barbara
Abstract : Purpose: The purpose of this study is to verify the possibility of applying alumina (Al2 O3 ) as the passivation and antireflective coating in silicon solar cells. Design/methodology/approach: Model of a studied structure contains the following layers: Al2 O3 /n+/n-type Si/p+/Al2 O3 . Optical parameters of the aluminium oxide films on silicon wafers were measured in the range of wavelengths from 250 to 1, 400 nm with a spectrophotometer Perkin Elmer Lambda 900. The minority carrier lifetime at the start of the n-type Si base material and after each of the next technological process was analysed by a quasi-steady-state photoconductance technique. The electrical parameters of the solar cells fabricated with four different thickness of the Al2 O3 layer were determined on the basis of the current-voltage (I-V) characteristics. The silicon solar cells of 25 cm 2 area and 300 µm thickness were investigated. Findings: The optimum thickness of alumina as passivation layer is 90 nm. However, considering also antireflective properties of the first layer of a photovoltaic cell, the best structure is silicon with alumina passivation layer of 30 nm thickness and with TiO2 antireflective coatings of 60 nm thickness. Such solution has allowed to produce the cells with the fill factor of 0.77 and open circuit voltage of 618 mV. Originality/value: Measurements confirmed the possibility of applying the Al2 O3 as a passivation and antireflective coating (obtained by atomic layer deposition method) for improving the efficiency of solar cells.